Antimicrobial Mechanisms in Plant Extracts: An In-Depth Analysis of Six Bioactive Compounds Against Listeria Monocytogenes - Jalil, Bilal Saad; Mahdi, Zahida Hatif; Ijmayyil, Zinah Jawad; Hammoodi, Kawther Abed; Jebur, Noor Hussein (Kerbala Journal of Nursing and Health Sciences., 2025)
Listeria monocytogenes constitutes a significant concern to food safety, particularly in refrigerated ready-to-consume products. With the increasing consumer demand for natural preservatives and minimally processed product compositions, investigation of plant-derived antimicrobial compounds has gned considerable interest. This study presents a comprehensive assessment of six plant-derived bioactive compounds: xanthohumol and alpha acids from hop (Humulus lupulus), oleanolic acid and tyrosol from olive (Olea europaea), and two sage (Salvia officinalis) extracts (SAL FR2 and Rosmarinic acid). Minimum inhibitory concentrations (MICs) were determined using broth microdilution assays, while growth kinetics and viability analyses provided additional insights into their mechanisms of action. Our findings highlight the efficacy of xanthohumol and oleanolic acid as potential candidates for incorporation into natural food preservation systems. Detled analysis of dose-response relationships, bacterial membrane integrity, and synergistic antimicrobial effects expands our understanding of these agents. This study supports the application of these natural compounds in food safety interventions. Listeria monocytogenes, antimicrobial activity, plant extracts, minimum inhibitory concentration, hop acids, oleanolic acid, food safety.